Optimasi pola operasi Waduk Tukul di Pacitan untuk mendukung kebutuhan air irigasi dan domestik - Imam Nashrullah; Hari Nugroho; Kresno Wikan Sadono (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Tukul Reservoir, located in Pacitan Regency, serves a strategic role as a multipurpose infrastructure designed to meet irrigation and domestic raw water requirements. However, climate change dynamics and fluctuations in inflow discharge necessitate a precise storage management strategy to guarantee service reliability. This study aims to analyze and optimize the operation patterns of Tukul Reservoir to achieve high reliability in fulfilling irrigation water needs for 153 hectares and an average domestic raw water demand of 242.95 liters/second. The research methodology employs a water balance optimization simulation based on the Standard Operating Rule (SOR) principle, utilizing a 25-year hydrological dataset. Simulations were conducted across various hydrological conditions—wet, normal, and dry years—applying a Rice-Rice-Secondary Crop (Padi-Padi-Palawija) cropping pattern starting in the third week of October (October III). The results indicate that during wet years, water supply reliability reaches an absolute level of 100%. In normal years, the reliability index is recorded at 83.33%, providing maximum service across all sectors. Conversely, during dry years, reliability decreases to 81.82%, where the reservoir can only supply 90% of the maximum raw water demand (219.00 liters/second). These findings recommend the implementation of a rotational irrigation system during dry periods to maintain the stability of crop water availability. Overall, the resulting operation patterns serve as a technical benchmark for dam authorities in optimizing sustainable water resource management.